Distribuicao dos saltos parciais na prova de salto triplo masculino e feminino - analise biomechanica - Moura, N. A. Q.; Duarte, M.; Mochizuki, L.; Amadio, A. C.
Although it remains barely investigated, the triple jump has been recognized as the voluntary human activity which produces the highest levels of stress into the body. Both researchers and coaches agree that the jumping ratios represent a determinative factor of performance. The present investigation had the purpose of presenting the triple jump ratios of elite level jumpers, both male and females, who was in action during Grand Prix Mobil-Banespa de Atletismo de São Paulo in 1994. Pearson's correlation analysis had showed, to male jumpers, that the Step had the highest correlation's phase with the total distance (r=0.70), while both Hop and Jump had smaller values (r=0.43 and r = 0.37, respectively). When we had considered female athletes, we had opposite findings: Hop and Jump showed higher values (r = 0.86 and r = 0.73, respectively), than the Step (r = 0.44). It is interesting to note that still there is not a technical or scientifical explanation to such discrepancy between the correlational values. Studying selected cases, we can see that athletes with the best perfomances can better reproduce their jumpings than lower performancers. Not being very consistent in the technic of jumping may indicate that they did not reach their optimum technique.